Increase maize productivity and water use efficiency through application of potassium silicate under water stress - Gomaa, M. A. (Sci Rep, 2021)
In Egypt, water shortage has become a key limiting factor for agriculture. Water-deficit stress causes different morphological, physiological, and biochemical impacts on plants. Two field experiments were carried out at Etay El-Baroud Station, El-Beheira Governorate, Agriculture Research Center (ARC), Egypt, to evaluate the effect of potassium silicate (K-silicate) of maize productivity and water use efficiency (WUE). A split-plot system in the four replications was used under three irrigation intervals during the 2017 and 2018 seasons. Whereas 10, 15, and 20 days irrigation intervals were allocated in main plots, while the three foliar application treatments of K-silicate (one spray at 40 days after sowing; two sprays at 40 and 60 days; and three sprays at 40, 60, and 80 days, and a control (water spray) were distributed in the subplots. All the treatments were distributed in 4 replicates. The results indicated that irrigation every 15 days gave the highest yield in both components and quality. The highly significant of (WUE) under irrigation every 20 days. Foliar spraying of K-silicate three times resulted in the highest yield. Even under water-deficit stress, irrigation every fifteen days combined with foliar application of K-silicate three times achieved the highest values of grain yield and its components. These results show that K-silicate treatment can increase WUE and produce high grain yield requiring less irrigation.